El comercio de ganado vacuno en la provincia de León durante la Edad Moderna - Pérez Álvarez, María José (Estudios humanísticos. Geografía, historia y arte, 1998)
The objective of this work to analyse the cattle's sold in the fairs of the city of León geographic origin, as well as the paper these fairs had in the commercial cattle market from the north of the peninsula. Other aspects treated are: the cattle-seller figure and the bovine races evolution in the area.